Effectiveness of Recovery-Oriented cognitive therapy on Emotion Recognition and Quality of Life in Patients with Schizophrenia - Saeedi, Morteza; Sharifidaramadi, Parviz; Sharifirad, Gholamreza (Health Nexus, 2024)
The purpose of this study was to investigate the effectiveness of recovery-oriented cognitive therapy on emotion recognition and quality of life in patients with schizophrenia. The research method was a quasi-experimental design with a pre-test, post-test, and follow-up with a control group. The study population included all schizophrenia patients hospitalized in round-the-clock neuro-psychiatric centers in Tehran in the year 2022. The sample size consisted of 30 individuals (15 in the experimental group and 15 in the control group) selected from the population using convenience sampling and were allocated to either the control or experimental groups. For the experimental group, recovery-oriented cognitive therapy was administered while the control group remained on a waiting list. The research tools included the Facial Emotion Recognition Test (Ekman & Friesen, 1976) and the Quality of Life Questionnaire (World Health Organization, 1996). The results indicated that recovery-oriented cognitive therapy had a significant impact on emotion recognition and quality of life in the post-test and follow-up stages. The findings of this research provide useful information regarding recovery-oriented cognitive therapy, and psychologists and psychiatrists can use this intervention to improve emotion recognition and quality of life in patients with schizophrenia.